Hydrotherapy as an evidence-based nursing intervention for managing type 2 diabetes mellitus: An integrative review - Yutika Wiguna; Nursiswati Nursiswati; Kusman Ibrahim (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Type 2 diabetes mellitus (DM) is a major global health challenge. Effective management requires non pharmacological interventions in addition to medication. Hydrotherapy, a non invasive and affordable water-based therapy, shows promise in improving blood glucose, insulin sensitivity, and vascular function. This review identifies hydrotherapy interventions for type 2 DM and evaluates their clinical impact. Purpose: To analyze how to improve adherence in type 2 diabetes mellitus patients in implementing the five pillars of diabetes mellitus management. Method: This integrative reviews the size devidence on hydrotherapy for type 2 DM, guided by two questions: